ANALISIS KESIAPAN GURU DALAM BERADAPTASI TERHADAP KURIKULUM MERDEKA - Mawaddah, Alfiani; Afifah, Haya Nisrina; Nurhalizah, Siti; Putra, Muhammad Jaya Adi; Sari, Mutia Yulita (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to analyze teachers' readiness to adapt to the Merdeka Curriculum at SDN 183 Pekanbaru. The research employed a qualitative method, using direct interviews with four teachers and one principal. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that although the teachers have understood the basic concepts of the Merdeka Curriculum, there are gaps in its technical implementation, particularly in terms of pedagogical readiness. Teachers are still accustomed to conventional teaching methods that focus on repetition rather than the facilitation of knowledge. They also require more time and additional training to effectively apply student-centered learning approaches. Furthermore, challenges remain in utilizing diverse learning resources and implementing comprehensive assessment methods. Support from the school environment—such as training programs and adequate infrastructure—is crucial to enhance teachers’ readiness to implement the Merdeka Curriculum effectively.